Maintenance of Water ATMs and Selection of locations for the Water ATMs on basis of Internal factors of the Location using Graph Theory - et. al., Nayeemuddin Ahmed (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Under the Smart City Project, Guwahatians got facility of Water ATMs. In this research main aim is to find out the optimal locations in the city on the basis of internal factors of the location (like quantity and quality of water etc.) so that maximum number of citizens avail the benefits of water ATM. There are sets of Water ATMs that cannot be taken down together, because they have certain critical functions like -installation of new software, update of existing software, installation of required equipment, raw water supply problem, maintenance of pipelines, change the capacity of water tanks, electricity problem, plumbing or all routine maintenance etc. This is a typical scheduling application of graph coloring problem. It turned out that 3 colors were good enough to color the graph of 12 nodes. So they could install updates in 3 passes.